2020
DOI: 10.3390/microorganisms8121988
|View full text |Cite
|
Sign up to set email alerts
|

Filling the Void: An Optimized Polymicrobial Interkingdom Biofilm Model for Assessing Novel Antimicrobial Agents in Endodontic Infection

Abstract: There is a growing realization that endodontic infections are often polymicrobial, and may contain Candida spp. Despite this understanding, the development of new endodontic irrigants and models of pathogenesis remains limited to mono-species biofilm models and is bacterially focused. The purpose of this study was to develop and optimize an interkingdom biofilm model of endodontic infection and use this to test suitable anti-biofilm actives. Biofilms containing Streptococcus gordonii, Fusobacterium nucleatum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…It was found that although there were differences in biofilm formation on the various parts of the tooth, generally the PMBs grew better in the microaerophilic atmosphere. Similarly, when the influence of different atmospheric condition (aerobic, 5% CO 2 , and anaerobic -85% N 2 , 10% CO 2 , 5% H 2 ) was evaluated on PMBs consisting of C. albicans-S. gordonii-Fusobacterium nucleatum-Porphyromonas gingivalis (Abusrewil et al, 2020), it was found that the greats biofilm formation occurred under 5% CO 2 conditions. This may be due to the ability of both S. gordonii and C. albicans to grow well under this condition.…”
Section: Influence Of Environmental and Host Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that although there were differences in biofilm formation on the various parts of the tooth, generally the PMBs grew better in the microaerophilic atmosphere. Similarly, when the influence of different atmospheric condition (aerobic, 5% CO 2 , and anaerobic -85% N 2 , 10% CO 2 , 5% H 2 ) was evaluated on PMBs consisting of C. albicans-S. gordonii-Fusobacterium nucleatum-Porphyromonas gingivalis (Abusrewil et al, 2020), it was found that the greats biofilm formation occurred under 5% CO 2 conditions. This may be due to the ability of both S. gordonii and C. albicans to grow well under this condition.…”
Section: Influence Of Environmental and Host Factorsmentioning
confidence: 99%
“…One of the host niches that is almost synonymous with biofilms is the oral cavity and several models for PMB formation have recently been developed to more closely approximate the conditions in the host. These models include models that better mimic the availability of nutrients (Montelongo-Jauregui et al, 2016), the oxygen levels present in root canals (Toral et al, 2017;Abusrewil et al, 2020) as well as the various bacteria associated with either caries or soft tissue infection in vitro (Abusrewil et al, 2020;Young et al, 2021). In addition, commercially available organotypic oral mucosal models have been used to study the interaction between C. albicans and bacteria (Krishnamoorthy et al, 2020).…”
Section: Advances In Models Used To Characterize Polymicrobial Biofilmsmentioning
confidence: 99%
“…It must remain active in the presence of pus, blood, and other biological fluids. It should be noted that, in addition to the optimal antimicrobial spectrum of action, the ‘ideal irrigant’ should act on the organic components of the biofilms and the inorganic components of the lubricated layer for better disinfection and penetration of siler into dentine tubules [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…An established interkingdom endodontic biofilm model, previously described by our group, was used throughout this study [ 36 ]. Briefly, biofilms containing Candida albicans SC5314 (ATCC MYA-2876), Streptococcus gordonii (ATCC 35105), Porphyromonas gingivalis (ATCC 33277) and Fusobacterium nucleatum (ATCC 10953) were constructed.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have shown that the antimicrobial effect of calcium-silicate-based sealers was enhanced by the incorporation of chitosan nanoparticles (CNps) in root canal sealers [ 29 , 34 ]. We and others have also shown the antimicrobial effectiveness of chitosan when used as a root canal irrigant [ 30 , 35 , 36 ]. Therefore, in the current study, we aimed to assess the anti-biofilm effects against complex polymicrobial biofilms of chitosan when incorporated into endodontic calcium silicate cements.…”
Section: Introductionmentioning
confidence: 99%